2019
DOI: 10.1038/s41419-019-1810-z
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA DANCR regulates proliferation and migration by epigenetically silencing FBP1 in tumorigenesis of cholangiocarcinoma

Abstract: Recently, long noncoding RNAs (lncRNAs) have been shown to play significant regulatory roles in human tumorigenesis. However, the biological function of lncRNAs in cholangiocarcinoma (CCA) remains largely unknown. In this study, DANCR was shown to be significantly upregulated in CCA. DANCR regulated the proliferation and migration of CCA cells in vitro. Moreover, downregulation of DANCR suppressed CCA cells proliferation in vivo. RNA-seq revealed that DANCR knockdown preferentially affected genes linked with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…One of which, the lncRNA ENSG00000226950, that has attracted the attention of several groups had previously been identified as a non-coding RNA associated with enhancer of zeste homolog 2 and was found to repress the runt related transcription factor 2 gene ( 81 ) and was called DANCR (Differentiation Antagonizing Non-Protein Coding RNA). The DANCR gene is bound by MYC when MYC is induced in the P493-6 cells in a time-dependent manner which is consistent with the findings of Hart et al ( 73 ) and other studies that followed DANCR expression in several tumors ( 82 89 ). Of interest here is the finding that DANCR plays a role in Acute Myeloid Leukemia (AML) ( 90 ).…”
Section: Myc Regulated Lncrnassupporting
confidence: 90%
“…One of which, the lncRNA ENSG00000226950, that has attracted the attention of several groups had previously been identified as a non-coding RNA associated with enhancer of zeste homolog 2 and was found to repress the runt related transcription factor 2 gene ( 81 ) and was called DANCR (Differentiation Antagonizing Non-Protein Coding RNA). The DANCR gene is bound by MYC when MYC is induced in the P493-6 cells in a time-dependent manner which is consistent with the findings of Hart et al ( 73 ) and other studies that followed DANCR expression in several tumors ( 82 89 ). Of interest here is the finding that DANCR plays a role in Acute Myeloid Leukemia (AML) ( 90 ).…”
Section: Myc Regulated Lncrnassupporting
confidence: 90%
“…Recently, lncRNAs have gained great attention as its role in CCA 15 . Several known lncRNAs were reported to be dysregulated in CCA tissues and involved in the CCA development and progression, such as DANCR 16 , PVT1 17 , and RMRP 18 . Recent studies have reported that SNHG6 is highly expressed in variety of cancer tissues (except CCA) and .…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are able to regulate the proliferation, apoptosis, migration and invasion of human cancer cells [9,10]. For instance, lncRNA-DANCR regulates proliferation and migration by epigenetically silencing FBP1 in tumourigenesis of cholangiocarcinoma [11]. LncRNA-SNHG6 enhances cell proliferation, migration and invasion by regulating miR-26a-5p/MAPK6 in breast cancer [12].…”
Section: Introductionmentioning
confidence: 99%